Analisis pengaruh Covid-19 terhadap tingkat pengangguran di Provinsi Jawa Tengah - Oktaria Dwi Nur ‘Aini (Economics, Finance, and Business Review, 2025)
Central Java Province is one of the provinces in Indonesia that is facing problems related to unemployment. The purpose of this study is to determine how the unemployment rate in Central Java Province is affected by COVID-19 and several other variables, namely GRDP, investment, Government Expenditure, and education. The research period is 2016-2020. This study uses panel data regression analysis as its research methodology. The findings show that COVID-19 increases the unemployment rate while government spending decreases the unemployment rate in Central Java. The variables GRDP, investment, and education do not affect the unemployment rate in Indonesia. The implication is that local governments must prepare strategies to mitigate unemployment problems if there is macroeconomic turmoil such as COVID-19.